Cent ans de prison : les conditions et les « privilèges » des détenus hommes, femmes et enfants - Laplante, Jacques (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
The creation of the prison in the xixth century cannot be dissociated from the misery and distress it inflicts on a group of men, women and children who are already (in various ways) in a minority position in society. Reform after reform of Quebec prisons over more than a hundred years have not created a milieu without this misery and distress as though these were an inherent part of prison life itself. How, then, explain the persistance in wanting to keep such an institution whose objective was the moral rectification of the individual and insisted on rehabilitating him ?